Study on the Guidance Strategies of Role Play in Kindergarten Middle Class - Chen, Xiaofeng (Transactions on Social Science, Education and Humanities Research, 2023)
Role play is the most typical play in early childhood from 3 to 5 years old, and is typically creative and symbolic. Role play is a stage of play that young children inevitably go through in their normal development, from which they gain cognitive, emotional and social development. Effective teacher's guidance is conducive to the overall improvement of children's play level, which promotes their ability to come up with play themes, choose and assign roles, use materials and toys, interact with roles, and cooperate, etc. It also improves children's play organization ability, gives full play to children's autonomy and creativity, and promotes the development of language and sociality.